Relation of attachment styles and cognitive emotion regulation strategies to depression in patients with chronic skin diseases - Razieh Lotfi; Ahmad Alipoor; Morteza Tarkhan; Vali Allah Farzad; Masoud Maleki (Gonabad University of Medical Sciences, 2017)
Skin is a vital organ for communication throughout the life cycle, so that skin disease can cause a significant psychological distress. This study aimed to assessment the relation of attachment styles and cognitive emotion regulation strategies to depression in patients with skin diseases. The 200 participants were selected using purposeful sampling among patients diagnosed with psoriasis, atopic dermatitis, and chronic idiopathic urticaria and who referred to dermatology clinics or phototherapy units of the hospitals in Mashhad. Patients who had inclusion criteria participated in the study after giving the informed consent. The participants filled out the scales of cognitive emotion regulation strategies, Collins and Read attachment styles, and hospital anxiety and depression. The results of path analysis showed a direct relation of secure attachment style to adaptive cognitive emotion regulation strategies and depression, cognitive emotion regulation strategies to depression, insecure attachment styles to maladaptive cognitive emotion regulation strategies, insecure attachment to depression, and maladaptive cognitive emotion regulation strategies to depression. Secure attachment had indirect effect on depression and insecure attachment had indirect relation to depression. These results imply that attachment styles and cognitive emotion regulation strategies in patients with skin diseases have multiple relations with depression.